Effect of Visual Merchandising, Store Atmosphere, and Price Discount on Impulse Buying with Positive Emotion as Intervening Variable - Raden Hanif Arga Suryana; Dewi Komala Sari (Indonesian Journal of Law and Economics Review, 2021)
This study aims to know the effect of Visual Merchandising, Store Atmosphere and Price Discount on Impulse Buying with Positive Emotion as an Intervening Variable in Ace Hardware Sidoarjo. The sample used were 100 respondents. Samples were taken by purposive sampling method. Data analysis technique is done by using PLS-SEM analysis with the SmartPLS 3.0 program. The results of this study indicate that Visual Merchandising has an effect on Impulse Buying, Store Atmosphere has an effect on Impulse Buying, Price Discount has no effect on Impulse Buying, Visual Merchandising has an effect on Positive Emotion, Store Atmosphere has an effect on Positive Emotion, Price Discount has an on effect on Positive Emotion, Positive Emotion has an effect on Impulse Buying, Visual Merchandising has an effect on Impulse Buying through Positive Emotion, Store Atmosphere has an effect on Impulse Buying through Positive Emotion, Price Discount has an effect on Impulse Buying through Positive Emotion